Покарання як складова системи соціального контролю над злочинністю - Крисюк, Ю.; Krysyuk, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статті розглядається поняття «соціальний контроль над злочинністю», а також роль покарання в системі соціального контролю. Аналізується «криза покарання» в сучасному світі та засоби мінімізації негативних наслідків позбавлення волі. Подано пропозиції щодо удосконалення кримінальної політики держави. Thearticle discusses the concept of «social control over crime» and the role of punishment in the social control system. It has been proved that at all times the state and society tried to minimize (eliminate and overcome) inadmissible to the community forms of the individuals behavior. In every country for this purpose there has always existed a system of social control over crime and other forms of negative deviance (drunkenness, drug addiction, prostitution, corruption and so on). However, none of the unacceptable negative social phenomena, including crime, has been «eliminated». The author believes that Emile Durkheim’s thesis that «crime is a common phenomenon in the society and itis quite impossible to find a society without crimes» is true and states that the only thing we can speak of is social control over the crime. Control of the crime is one of the forms of social control and may be considered as a mechanism of self-organization (selfregulation), and self-preservation of society by establishing and maintaining regulatory order in the community and implies the elimination, neutralization or minimization of the deviant behavior of its members.
Punishment as an Integral Part of the Social Control over the Crime
Keywords: злочин; покарання; соціальний контроль; злочинність; «криза покарання»; crime; punishment; social control; crime; the crisis of punishment